Editorial: Convergence of multiple pathways in PSGL-1 activation and leukocyte transmigration: therapeutic implications. Issue 4 (1st October 2017) - Velasquez, Stephani; Rappaport, Jay
Abstract : Discussion on the implications regarding leukocyte inflammation, and potential therapeutic approaches.